Black political activism and the Cuban republic - Pappademos, Melina (Envisioning Cuba., 2011)
While it was not until 1871 that slavery in Cuba was finally abolished, African-descended people had high hopes for legal, social, and economic advancement as the republican period started. This book analyses the racial politics and culture of black civic and political activists during the Cuban Republic. The path to equality, the author reveals, was often stymied by successive political and economic crises, patronage politics, and profound racial tensions.